Ruta chalepensis L. Essential Oil: A New Antisprouting Agent for Potatoes Bioconservation - Olfa Lengliz; Jamel Mejri; Manef Abderrabba; Rachid Khalifa; Mondher Mejri (Journal of Chemistry)
The main concern of this work was to find a new biological antisprouting product for potatoes during storage. Ruta chalepensis L. essential oil (RCEO) was for the first time used as a potential sprouting inhibitor for potatoes. To confirm RCEO antisprouting effect, evolution of sprout length and weight loss of potato tubers was determined during a storage period of six weeks under three RCEO different treatments (2%, 4%, and 6%). Sprout final weight was also computed. Then, a screening of RCEO chemical composition was performed. An outstanding antisprouting effect of 6% emulsions concentrations was observed as compared to 2% and 4% emulsions concentrations. Final sprout weight (SW) of untreated samples was 4.66%, while 6% treated samples scored 0.98%. These results were endorsed by high Pearson correlation coefficients (>0.9). Indeed, increasing treatment concentration enhanced the sprout growth inhibition. Identification of RCEO major components showed that 2-undecanone represented 87.18% of total identified components suggesting that this component is the possible active agent of RCEO against potatoes sprouting.